Collaborative strategies for sustainable management of the Citarum Watershed in Indonesia: a Quintuple Helix approach - Abdillah Abdillah; Ida Widianingsih; Rd Ahmad Buchari; Heru Nurasa (Discover Sustainability)
Abstract The Citarum River revitalization program through the “Citarum Harum” program, focuses on integrated cooperation between multi-sector actors in managing the Citarum Watershed sustainably and improving the quality of life around the river. Such as ministries (central government) acting as policy and regulation providers and as the leading sector, local governments acting as program supervisors and monitors, academics/universities acting as knowledge creators and program management innovations, the private sector acting as important partners, communities acting as program supporters and participants, and the Indonesian National Army (Tentara National Indonesia, TNI) acting as initiators, law enforcers, and field supervisors. This article outlines some of the challenges faced by Citarum Watershed, as well as important findings regarding collaborative sustainable and resilient watershed management, particularly in the context of the Citarum River, Indonesia. In this commentary, we underscore the importance of collaborative efforts, effective policy frameworks, and adaptive management strategies in addressing the environmental challenges faced by the Citarum River, while highlighting the need for ongoing commitment from all stakeholders during program implementation and post-program. The implications of these findings suggest a holistic, inclusive, and adaptive approach to sustainable management of watersheds and the environment that can be applied to other regions facing similar challenges such as Pollution; Environmental Degradation; Critical Land and Sedimentation; Inadequate Infrastructure; Population Growth and Urbanization; Climate Change, Weak Law Enforcement, and Lack of Coordination Among Stakeholders.